2015
DOI: 10.1177/1559325815598308
|View full text |Cite
|
Sign up to set email alerts
|

Global Assessment of Bisphenol A in the Environment

Abstract: Because bisphenol A (BPA) is a high production volume chemical, we examined over 500 peer-reviewed studies to understand its global distribution in effluent discharges, surface waters, sewage sludge, biosolids, sediments, soils, air, wildlife, and humans. Bisphenol A was largely reported from urban ecosystems in Asia, Europe, and North America; unfortunately, information was lacking from large geographic areas, megacities, and developing countries. When sufficient data were available, probabilistic hazard asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 575 publications
(199 citation statements)
references
References 507 publications
6
159
0
Order By: Relevance
“…7C the obtained T3-EQ values for the highest tested dose (100 μM) were just 0.9 nM and 5.9 nM for BPA and TBBPA, respectively. Considering the prevalent contamination of the environment with BPA worldwide (Corrales et al 2015) it is plausible that BPA could be also present in some of the tested water samples. Indeed, an earlier study found 12 μg/L BPA in effluents in the US water (Kolpin et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…7C the obtained T3-EQ values for the highest tested dose (100 μM) were just 0.9 nM and 5.9 nM for BPA and TBBPA, respectively. Considering the prevalent contamination of the environment with BPA worldwide (Corrales et al 2015) it is plausible that BPA could be also present in some of the tested water samples. Indeed, an earlier study found 12 μg/L BPA in effluents in the US water (Kolpin et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Bisphenol A (BPA) is a man-made compound highly prevalent in our environment and suspected to act as an endocrine disruptor [10]. It is intensively produced and used as a monomer of polycarbonate plastics and epoxy resins [11].…”
Section: Introductionmentioning
confidence: 99%
“…The general population, including pregnant women, can be exposed to BPA in their daily life through food and drinking water, and non-dietary sources, such as toys and cosmetics [60]. In many countries [61], including A r g e n t i n a ( h t t p : / / w w w. a n m a t . g o v. a r / b o l e t i n _ anmat/BO/Disposicion_1207-2012.pdf), the use of polycarbonate in baby bottles has been banned.…”
Section: Discussionmentioning
confidence: 99%